2016
DOI: 10.18549/pharmpract.2016.04.822
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy after solid-organ transplantation: does the INTERMED identify patients at risk of poor adherence?

Abstract: Background:Lack of adherence to medication is a trigger of graft rejection in solid-organ transplant (SOT) recipients.Objective:This exploratory study aimed to assess whether a biopsychosocial evaluation using the INTERMED instrument before transplantation could identify SOT recipients at risk of suboptimal post-transplantation adherence to immunosuppressant drugs. We hypothesized that complex patients (INTERMED>20) might have lower medication adherence than noncomplex patients (INTERMED≤20).Methods:Each patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(67 reference statements)
1
2
0
1
Order By: Relevance
“…This sample’s IS non-persistence rate (i.e., discontinuation of the regimen) was very low ( N = 7, 0.5%). This finding echoed those of other studies, all of which reported very small prevalence (0.6%–3.1%) of medication non-persistence [ 17 , 18 , 49 ]. In all cases, including cases with a high relative rate of missing information on INA—e.g., Spain, Italy, Germany—, the number of cases involved were too low to allow in-depth analyses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This sample’s IS non-persistence rate (i.e., discontinuation of the regimen) was very low ( N = 7, 0.5%). This finding echoed those of other studies, all of which reported very small prevalence (0.6%–3.1%) of medication non-persistence [ 17 , 18 , 49 ]. In all cases, including cases with a high relative rate of missing information on INA—e.g., Spain, Italy, Germany—, the number of cases involved were too low to allow in-depth analyses.…”
Section: Discussionsupporting
confidence: 86%
“…To date, though, INA to IS (which we will refer to simply as INA) has received only limited attention in the HTx populations and has not been well-substantiated due to inconsistent definition and measurement and large international variability. INA has not been directly studied, and estimated prevalence of drug holidays or non-persistence to IS vary widely, respectively 0%-7.1% and 0.6%-3.1% [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…While studies have mentioned the impacts of pre-transplant depression in non-adherence of liver and kidney transplant recipients (Scheel et al, 2018;Golfieri et al, 2019), they have suggested the positive impact of psychological interventions in adherence. It is also noticeable that in some studies, poor psychological scores before transplantation did not significantly modify patient adherence to immunosuppressive regimens when compared with psychologically stable patients (Michaud et al, 2016). This suggests further attention to considering the causal relationship between non-adherence and poor psychological scores.…”
Section: Discussionmentioning
confidence: 96%
“…Estudos de confiabilidade interavaliadores apresentaram os seguintes resultados: Posteriormente, foi validado para diversas patologias -dor lombar, diabetes, pacientes em cuidados paliativos, esclerose múltipla, e com traumas ortopédicos. (MICHAUD et al, 2016;SCERRI et al, 2006;VOUILLOZ et al, 2011). Também para pacientes urológicos (quanto à versão auto aplicável) (DI GANGI HERMS et al, 2003;WILD et al, 2011); com pacientes espanhóis com câncer, problemas pulmonares e internados em enfermarias hospitalares (KOCH et al, 2001;LOBO et al, 2007LOBO et al, , 2008LOBO et al, , 2013; no contexto de urgência e emergência na Áustria (MATZER et al, 2012); e nos Estados Unidos no contexto terciário para uso de Gerentes de Caso (KATHOL; HOBBS MELLLER et al, 2015), no Canadá na versão pediátrica (NADER, 2020), e na versão autoaplicável para idosos na Holanda No Brasil, a pesquisa de validação do INTERMED teve início através da pesquisadora Bernadete Weber (WEBER et al, 2012), no contexto hospitalar e com pacientes idosos (GUTIERREZ; SILVA; SHIMIZU, 2014), sendo realizado um estudo de tradução, adaptação transcultural e validação, cujo processo será descrito a seguir.…”
Section: Processo De Desenvolvimento E Análise Dos Valores Psicométricos Do Intermedunclassified